Non-nutrient heavy metals in tomato plants cultivated in soil amended with biosolid and sugar-cane bagasse compost - Cintra, A. A. D. [UNESP]; Revoredo, M. D. [UNESP]; Melo, W. J. [UNESP]; Braz, L. T. (My University, 2004)
In this study, non-nutrient heavy metal concentrations (Cd, Cr, Ni and Pb) were measured in composts during the composting process, in compost/Red-yellow Latosol mixtures, and in tomato plants. Composts were produced using sugar-cane bagasse, biosolids and cattle manure in the proportions 75-0-25, 75-12.5-12.5, 75-25-0, 50-50-0 or 0-100-0 (composts with 0, 12.5, 25, 50 and 100% biosolids). The composts were applied to the soil, in 6 treatments and a control (mineral fertilization). Control and the 0% biosolids treatments received inorganic nitrogen and all the treatments received the same amount of N, P and K. Tomato plants were cultivated in 24-L pots, in a green house in Jaboticabal, SP, Brazil. The experiment had a split plot design, in randomized blocks. Cadmium, Cr, Ni and Pb concentrations were determined during the composting process (7, 27, 57, 97 and 127 days after compost mounting), in soil (0 and 164 days after mixing) and plants. The samples were subjected to digestion with HNO 3, H2O2 and HCl and the metals were determined by AAS. Negative correlations were observed between Cd, Cr and Pb in the compost and Cd, Cr and Pb plant uptake, as well as Ni in the compost and Ni concentration in the plants. The concentrations of Cd, Cr, Ni and Pb increased during composting. Only Cd levels increased when compost was applied to the soil. The roots accumulated Cr, Ni and Pb, the stems and leaves, Cd and Ni and the fruits did not accumulate any of the metals studied. The composts with biosolids did not increase Cd, Cr, Ni and Pb uptake by plants.
Keywords: Cd; Compost; Cr; Lycopersicon esculentum; Ni; Pb; Waste